FACTORS PREDICTING QUALITY OF LIFE IN CHRONIC NCDS CLINIC HUASAI HOSPITAL, HUASAI DISTRICT, NAKHON SI THAMMARAT PROVINCE - Thusaneesuwan, Uraiwan (Journal of MCU Nakhondhat, 2021)
The objective of this research was to study of quality of life level and determine the predictive of quality of life of elderly in chronic NCDs clinic Hua Sai Hospital, Hua Sai District, Nakhon Si Thammarat Province. The samples were 321 patients, aged 60 years and over who were treated in chronic NCDs clinic. Huasai Hospital, Hua Sai District, Nakhon Si Thammarat Province. They were selected by using the formula of Krejcie & Morgan. The research questionnaire consisted of 1) General data questionnaire, namely personal data, health condition and health care, 2) Thai Geriatric Depression Scale: TGDS, which the alpha Cronbach coefficient = 0.87 and 3) Quality of Life Assessment, that using Hamtanon, P. et al (2020) quality of life assessment, alpha Cronbach coefficient = 0.88. Data were collected from December, 2020 to January, 202. Data were analyzed using frequency, Percentage, Mean, standard Deviation and stepwise multiple regression analysis. The results showed that 1) the overall quality of life level of most of the elderly subjects had good quality of life and 2) predictive factors of quality of life of the elderly in chronic non - communicable disease clinic were depression, good health, primary education, secondary education, frequent participation in social activities and age, which all factors could predict quality of life with 31.60% (R2 = .316, p <.001).